Educational cosmopolitanism and collaborative inquiry with Chinese and US teachers. Issue 4 (2nd October 2019) - Spires, Hiller A.; Kerkhoff, Shea N.; Fortune, Nicholas
ABSTRACT: As the world becomes more interconnected, educators have opportunities to collaborate across cultures. Using the theory of educational cosmopolitanism and the pedagogy of collaborative inquiry, this collective case study explores how Chinese and American teachers perceive the assets and challenges of conducting collaborative inquiry with their students across cultures, and how they collaboratively planned in order to conduct these inquiries. Results demonstrated both assets (i.e. promotion of global citizenship and interpersonal skills) and challenges (i.e. digital access and the need for sustainable external support). Additionally, results on how the teachers collaborated revealed the four dimensions of educational cosmopolitanism (i.e. hospitality, reflexivity, intercultural dialogue, and transactions of perspectives) were in play, although to varying degrees. The research sheds light on how educational cosmopolitanism holds promise as a potential theoretical lens for conducting collaborative inquiry with culturally and geographically diverse teachers and students.